Removal of point source leakage from time-order data filtering - Zhang, Zhaoxuan; Huang, Lu; Liu, Yang; Li, Si-Yu; Zhang, Le; Liu, Hao (Frontiers in Physics, 2023)
Time-ordered data (TOD) from ground-based CMB experiments is usually filtered before map-making to reduce the contamination from ground and atmospheric emissions. However, when the observation region contains strong point sources, the filtering process will cause a considerable leakage around the point sources, which should be eliminated to provide a clean CMB polarization map for scientific purposes. The method we introduce in this work, which we refer to as “template fitting,” is capable of removing these leakage signals in the pixel domain, meeting the requirement of measuring the primordial gravitational waves from CMB-B modes for at least r < 0.005, while also avoiding time-consuming operations on the TOD.